Utilization of Katuk Leaves (Sauropus androgynus) as an Herbal Food to Support Breast Milk Production in Breastfeeding Mothers: A Literature Review - Rahmah, Tatiya Riftiani; Halim Fawaz, Syahal; Turyadi, Itto (Madani: Jurnal Ilmiah Multidisiplin, 2026)
Insufficient breast milk production remains one of the obstacles to the success of exclusive breastfeeding. One of the local food ingredients widely used by the community to support breast milk production is katuk leaves (Sauropus androgynus). This study aims to analyze the utilization of katuk leaves as an herbal food to support breast milk production in breastfeeding mothers. The method used was a narrative literature review by examining three relevant articles regarding the effect of katuk leaves on breast milk production, the cultivation of katuk leaves as processed food ingredients, and the use of katuk as a herbal plant in the community. The results of the review indicate that katuk leaves have potential as a galactagogue because they contain compounds such as sterols, alkaloids, papaverine, flavonoids, vitamins, and minerals. Katuk leaves can also be processed into various forms, such as clear vegetable soup, decoctions, extracts, biscuits, and other food products. In addition, ethnobotanical studies show that the most common use of katuk leaves in the community is to promote breast milk production. Therefore, katuk leaves have the potential to be used as an herbal food to support breast milk production; however, their use should consider proper processing methods and safe consumption limits.